The majority of parents of overweight and very overweight children underestimate their child's weight status and weight-related health risk. (24th May 2012) - Falconer, C L; Skow, A; Black, J; Croker, H; Sovio, U; Kessel, A; Saxena, S; Viner, R; Kinra, S
Abstract : Aims: The aim of this study was to explore parents' perceptions of their child's weight status and weight-related health risks. Methods: The UK National Child Measurement Programme (NCMP) measures the height and weight of every child aged 5/6 and 10/11. Parents of children in the NCMP across five PCTs completed questionnaires prior to their child's measurement. Parents classified their child's current weight status into one of four categories (underweight, healthy weight, overweight or very overweight) and these classifications were compared to NCMP classifications using logistic regression with robust standard errors to account for clustering. Results: A total of 3050 parents completed the questionnaire. Over 99% of parents of healthy weight children correctly identified their child's weight status, compared to 12% of parents with overweight children and less than 1% of parents with very overweight children. Parents of overweight and very overweight children were less likely to correctly identify their child's weight status in children aged 5/6 years (OR: 5.25, 95% CI: 2.36-11.71), in boys (OR: 2.97, 95% CI: 1.43-6.18) and in very overweight children (OR: 32.9, 95% CI: 4.5-240.8). Correct classification was not associated with ethnicity, parental education or family history of obesity. The majority of parents with overweight and very overweight children (73%) reported general knowledge of health risks associated with childhood overweight. However, when applying this knowledge to their own child, only 22% identified their child's weight as a health risk. Among these parents, the odds of failing to identify a health risk in their child were higher in parents of overweight children than very overweight children (OR: 4.74, 95% CI 2.96-7.58) and in parents of children aged 5/6 (OR: 4.20, 95% CI: 2.56-6.90). There was no association between health risk perception and family history of disease or parental BMI. Conclusions: The majority of parents of overweight and very overweight children underestimate their child's weight status and associated health risk. Parents of younger children, boys and very overweight children were more likely to incorrectly classify their child's weight and fail to identify their child's weight as a health risk. This study highlights the need to address parental misperceptions as an important step to tackling overweight children.